Microfluidic PCR‐based target enrichment: A case study in two rapid radiations of Commiphora (Burseraceae) from Madagascar. Issue 5 (4th September 2015) - Gostel, Morgan R.; Coy, Kiera A.; Weeks, Andrea; Wen, Jun; Liu, Jianquan; Ge, Song; Xiang, Qiu‐Yun (Jenny); Zimmer, Elizabeth A.
Abstract Developing effective and cost‐efficient multilocus nuclear datasets for angiosperm species is a continuing challenge to the systematics community. Here we describe the development and validation of a novel set of 91 nuclear markers for PCR‐based target enrichment. Using microfluidic PCR and Illumina MiSeq, we generated nuclear, subgenomic libraries for 96 species simultaneously and sequenced them for a total cost of ca. $6000 USD. Approximately half of these costs include reusable reagents (primers, barcodes, and custom sequencing primers) and taxon sampling could be increased by an order of magnitude to maximize sequencing depth efficiency. The principle benefit of microfluidic PCR over alternative target enrichment strategies is that it bypasses costly library preparation. After sequencing, we evaluated the ability of the loci to resolve species level relationships within two recently radiated lineages of endemic Madagascan Commiphora Jacq. (Burseraceae) species. Our results demonstrate that (i) effective nuclear markers can be designed for non‐model angiosperm taxa from these publicly available datasets; (ii) that microfluidic PCR amplification followed by high throughput sequencing can produce highly complete taxon by locus sequence data matrices with minimal resource investment; and (iii) that these numerous nuclear phylogenomic markers can improve our understanding of phylogenetic relationships within Commiphora. We provide a synopsis of ongoing activities to enhance this microfluidic PCR‐based target enrichment strategy through broader primer assays, multiplexing, and increased efficiency of sequencing depth.